Short- vs. long-range elastic distortion: structural dynamics of a [2 × 2] tetrairon(ii) spin crossover grid complex observed by time-resolved X-Ray crystallography. Issue 46 (31st October 2022) - Velazquez-Garcia, Jose de Jesus; Basuroy, Krishnayan; Storozhuk, Darina; Wong, Joanne; Demeshko, Serhiy; Meyer, Franc; Henning, Robert; Techert, Simone
Abstract : Upon irradiation with a ps laser pulse, a [2 × 2] tetrairon(ii ) spin crossover grid shows two types of elastic distortions: a short-range distortion in ps regime and a long-range distortion in the ns time scale. Abstract : Spin crossover complexes (SCO) are among the most studied molecular switches due to their potential use in displays, sensors, actuators and memory components. A prerequisite to using these materials is the understanding of the structural changes following the spin transition at out-of-equilibrium conditions. So far, out-of-equilibrium studies in SCO solids have been focused on mononuclear complexes, though a growing number of oligonuclear SCO complexes showing cooperative effects are being reported. Here, we use time-resolved pink Laue crystallography to study the out-of-equilibrium dynamics of a [2 × 2] tetranuclear metallogrid of the form [FeII4L Me 4 ](BF4 )4 ·2MeCN ([L Me ] − = 4-methyl-3, 5-bis6-(2, 2′-bipyridyl)pyrazolate). The out-of-equilibrium spin state switching induced by a ps laser pulse demonstrates that the metallogrid exhibits a multi-step response similar to that reported for mononuclear complexes. Contrary to the mononuclear complexes, the metallogrid shows two types of elastic distortions at different time scales. The first is a short-range distortion that propagates over the entire Fe4 grid complex during the ps time scale, and it is caused by the rearrangement of the coordination sphere of the photo-switching ion and the constant feedback between strongly linked metal ions. The second is a long-range distortion caused by the anisotropic expansion of the lattice during the ns time scale, observed in mononuclear materials. The structural analysis demonstrates that the long-range prevails over the short-range distortion, inducing the largest deformation of both the entire grid and the coordination sphere of each metal ion. The present study sheds light on the out-of -equilibrium dynamics of a non-cooperative oligonuclear complex.